On Categories of Container Classifiers and the Marker Forms of “full/entire” in “one + container classifier + noun” Construction - Chamsuwanwong , Nattanit (Journal of Sinology (วารสารจีนวิทยา), 2012)
This paper aims to discuss the semantic interpretation of the numeral “one” in “one + container classifier + noun (one + CLc + N)” construction. When used with different categories of container classifiers, the numeral “one” in the “one + CLc + N” construction can be interpreted in two ways: one, it represents the “actual number”; or two, it expresses the meaning of “full/entire.” Container classifiers could be divided into three categories: numeral container classifiers (糖箱一 <one box sugar>, ‘a box of sugar’); ‘full’-numeral container classifiers (一桌子糖 <one table sugar>, ‘a tableful of sugar’); and, full covered container classifier(一地糖 <one ground/floor sugar>, ‘a floorful of sugar’). The last two categories of container classifiers can cause “one” to be interpreted as conveying “full/entire” meanings. Thus, these classifiers can be regarded as intrinsic markers for the “full/entire” meaning. However, when certain specific markers are added to the construction, such as “de(的)” , “dou(都)”, and certain negation markers; or if 一“yi” is replaced by “man(满)/quan(全)”, and not by other number, the meaning of “full/entire” will become the prominent one. These special markers are analyzed here as external markers.